An Especial Fractional Oscillator. (23rd June 2013) - Tofighi, A.
Abstract : We propose a peculiar fractional oscillator. By assuming that the motion takes place in a complex media where the level of fractionality is low, we find that the time rate of change of the energy of this system has an oscillatory behavior.